Estimación del consumo del ensilado de cebada forrajera con niveles de follaje de papa (Solanum tuberosum) y afrecho de trigo a partir de la fibra detergente neutra - Gomez Escobar, Edita (2023)
This research was serialized in the Laboratory of Animal Nutrition and Food Evaluation (LUNEA) of the Professional School of Zootechnics of the National University of Huancavelica, Peru, with the objective of estimating the consumption of forage barley silage with levels of potato foliage (Solanum tuberosum) and wheat bran from neutral detergent fiber. Forage barley samples with a chopped size of 4 to 6 cm were used, where potato foliage and wheat bran were added at different levels 0, 10, 20 and 30%. The chopped material was ensiled in bag-type mini-silos with a capacity of 5 kg for 30 days. After the fermentation time, the mini-silos were opened and samples were taken to evaluate the neutral detergent fiber and apply the prediction equation for consumption. of dry matter (CMS). An analysis of variance was used for the variables under study. The %FND was in the range of 47.29±4.03% to 42.80±6.63%, within the levels of 0 to 30% of potato foliage and wheat bran. In addition, values of 2.86% of DMC with respect to live weight were estimated when using the level of 30% of potato foliage and wheat bran. Finally, the use of barley silage with levels of potato foliage and wheat bran allows to have close values in % NDF for a better use in ruminants as well as adequate dry matter intake for its use.